2019
DOI: 10.1155/2019/4282754
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Impact of Magnetic Resonance Imaging (MRI) on Gross Tumor Volume (GTV) Definition for Radiation Treatment Planning (RTP) of Inoperable High Grade Gliomas (HGGs)

Abstract: Aim and Background. Inoperable high-grade gliomas (HGGs) comprise a specific group of brain tumors portending a very poor prognosis. In the absence of surgical management, radiation therapy (RT) offers the primary local treatment modality for inoperable HGGs. Optimal target definition for radiation treatment planning (RTP) of HGGs is a difficult task given the diffusely infiltrative nature of the disease. In this context, detailed multimodality imaging information may add to the accuracy of target definition i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 45 publications
(55 reference statements)
2
8
0
Order By: Relevance
“…Utility of multimodality imaging for radiosurgery treatment planning for tectal gliomas has been poorly addressed in the literature. In this context, our study adds to the existing literature and supports the incorporation of MRI for improved radiosurgery treatment planning for tectal gliomas consistent with another studies [48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Discussionsupporting
confidence: 86%
“…Utility of multimodality imaging for radiosurgery treatment planning for tectal gliomas has been poorly addressed in the literature. In this context, our study adds to the existing literature and supports the incorporation of MRI for improved radiosurgery treatment planning for tectal gliomas consistent with another studies [48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Discussionsupporting
confidence: 86%
“…In this study, we assessed incorporation of multimodality imaging into target volume definition of trigeminal neuralgia radiosurgery. Indeed, usefulness of neuroimaging with MRI for definition of central nervous system radiotherapy and radiosurgery target volumes has been an important focus of research in the literature [40][41][42][43][44][45][46][47][48][49]. Our results appear to be compatible to these studies supporting the incorporation of MRI in radiosurgery treatment planning.…”
Section: Discussionsupporting
confidence: 83%
“…In this context, multimodality imaging may add to the accuracy of target definition for radiosurgery of intracranial GCTs. Indeed several other studies have demonstrated refined treatment volume determination by including MRI to the process of target determination [39][40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Resultsmentioning
confidence: 99%